Effect of chlorhexidine, green tea and egcg as therapeutic primers to increase the durability of resin-dentin bond - Barcellos, Daphne Camara; Fonseca, Beatriz Maria; Bresciani, Eduardo; Pucci, Cesar Rogerio; Araujo, Maria Amelia Maximo de (Brazilian Dental Science, 2016)
Objective - This study evaluated the effect of 0.2% chlorhexidine gluconate solution (CHX), green tea and active epigallocatechin-gallate (EGCG) used as therapeutic primers on the long-term bond strength of etch-and-rinse adhesive to dentin. Material and Methods - Eighty bovine incisors were worn to expose an area of dentin, that were acid-etched (37% phosphoric acid) and rinsed. The teeth were divided into 4 groups (n = 20): Group C (Control) - Single Bond; Group CHX - 0.2% CHX for 30s + Single Bond; Group EGCG - active EGCG gel at 10 µM for 30 s + Single Bond; Group GT - aqueous green tea for 30s + Single Bond. Blocks of composite were fabricated and stored for 24 h or 6 months, sectioned into beams and submitted to microtensile tests. Results were analyzed by two-way ANOVA and Tukey’s test (5%). Results - Mean (±SD) values (in MPa) were as follow: CHX (24 h) – 41.76 (±2.62); C (24 h) - 40.81 (±3.35); GT (24 h): 37.38(2.98); CHX (6 months) - 36.04 (±3.52); EGCG (24h) - 35.91 (±4.82); EGCG (6 months) - 35.75 (±4.44); GT (6 months) - 31.95 (±3.40); C (6 months): 30.05 (±1.54). Conclusion - EGCG produced resin-dentin bonds that did not change after 6 months water storage but it decreased the immediate bond strength when compared to control and chlorhexidine groups. Keywords: Tensile bond strength; Dentin; Total-etch adhesives; Chlorhexidine gluconate; Green tea.